Дендрофлора міста Луцька: формування, видовий склад, біологічні та екологічні особливості - Шепелюк, Марія Олександрівна (НУБіП України, 2017)
Дисертація на здобуття наукового ступеня кандидата сільсько-господарських наук зі спеціальності 06.03.01 «Лісові культури та фітомеліорація». – Національний університет біоресурсів і природо-користування України, Київ, 2017. У дисертаційній роботі представлено результати аналізу та оцінки видового складу, фітосанітарного стану, біологічних та екологічних особливостей дендрорізноманіття насаджень міста Луцька. Уперше проведено інвентаризацію деревних та кущових рослин зелених насаджень різного функціонального призначення. Досліджено сезонні ритми росту і розвитку едифікаторів насаджень, встановлено зміни їхніх приростів та тривалість вегетаційних періодів у різних екологічних умовах. Оцінено загальновидову декоративність рослин деревних видів за сукупністю морфологічних ознак. Методом прямого лабораторного проморожування встановлено морозостійкість перспективних інтродукованих деревних видів. Методом індукції флуоресценції хлорофілу визначено функціональний стан листків рослин деревних видів залежно від еколого-фітоценотичних поясів міста. Згідно з літературними та архівними джерелами уточнено періодизацію формування дендрорізноманіття міста та охарактеризовано сучасний етап. Досліджено динаміку змін едафічних умов території міста, видового складу та стану за останнє десятиріччя формування. На основі результатів проведеного дослідження запропоновано шляхи розширення біорізноманіття. Подальший розвиток отримав моніторинг рослин міста
The thesis for awarding scientific degree of candidate of agricultural sciences in specialty 06.03.01 Forest Plantation and Phytomelioration. ‒ National University of Life and Environmental Sciences of Ukraine, Kyiv, 2017. The dissertation presents the results of analysis and evaluation of species composition, phytosanitary state, biological and ecological peculiarities of dendro-diversity of Lutsk planting. Since there are no fundamental comprehensive researches of tree diversity of different categories plantings, no registration and monitoring system of urban plants, inventory and assessment of the phytosanitary state of the dendroflora of Lutsk are revelant. In the dissertation, according to literary and archival sources, historical and stylistic genesis of greening development of the city is shown. The specified periodization of the formation of dendro-diversity is presented and the modern stage is described in details. The problems with the preservation of the existing general urban plantings in good state and gradual reduce of green areas are currently observed there. For the first time, an every single tree inventory of city plantings of different functional uses was conducted. According to the results, dendro-diversity of city is represented by 33 families, 66 genesis, 108 species, 1 subspecies and 26 cultivars, of these 73 % of plantings are occupied by introduced species and only 27 % – by native. Two divisions, Pinophyta and Magnoliophyta, are presented. It was marked the advantage of angiosperms ‒ 88 %, compared to the gymnosperms, which in species diversity occupies only 12 %. Dominant species of trees and shrubs of different plantings groups and the presence of hedges and vertical gardening in landscaping of Lutsk were reviled. During the dissertation researches the phytosanitary state of plantings was determined; the most common fauna, diseases and insects pests of trees were studied. Due to the uneven impact of urban factors on the development of green plants in different ecological zones of growth, the phenological observations of urban ecosystem engineer plants for seasonal rhythm of growth and development were conducted. The change of its growth and duration of vegetation periods in different places of growth were shown. According to the assessment of the decorativeness of plant species in a variety of morphological signs, the majority of studied species, which are the ecosystem engineers of urban phytocenosis of Lutsk, are medium decorative. The results of determining the functional state of plants leaves of tree species by chlorophyll fluorescence induction method were shown. It was established the influence of growth conditions and genotypic specificity on individual indicators of IFC leaves of studied species and coefficients characterizing the course of light phases of photosynthesis and the efficiency of photochemical processes for dark phases of light energy absorption. The frost resistance of promising introduced species for urban conditions of Lutsk was established by the method of direct laboratory freezing. According to the anatomical-microscopic estimation, certain regularities of damage of different tissues structures were noted: the largest indices of damage were obtained in the apical and middle parts of the shoot under the bud, which is characteristic for all experimental species. The dynamics of changes in the edaphic conditions of the city territory was marked. The gradual acidification takes place: the pH decreased to neutral and weakly alkaline value (6.2‒7.6) at most studied objects. The conducted agrochemical researches indicate the imbalance of the main nutritional elements in soils of Lutsk. The dissertation presents the results of experimental studies of heavy metals content in soils of the city, which show a significant excess of lead, cadmium and zinc in the city center and near the main highways. The changes of species composition and its state during the last decade of formation, that reflecting the modern reduction of areas of recreational zones and the dynamics of dendro-diversity were analyzed. Inventory materials can be used for recording and monitoring of urban green spaces of various functional uses. The proposals for the optimization of the species composition can serve as a scientifically grounded basis for the selection of species diversity for urban conditions. The unified methodology for studying the species composition, the present state and peculiarities of the dendro-diversity formation can be recommended for using in the greening system in all settlements. The complex of effective technological measures aimed at optimization of species composition and state of the main central parks of the city was introduced into the work of the Communal Enterprise «Parks and squares of Lutsk». The obtained results are used in care of tree species of green spaces of Lesya Ukrainka Central Park of Culture and Rest and Park of the 900th Anniversary of Lutsk in order to ensure its sustainable viability, decorativeness and biological stability. The main provisions and conclusions of the dissertation are used in the process of teaching the subjects «Decorative Dendrology», «Introduction and Adaptation of Woody Plants», «Form Variety of Ornamental Woody Plants» in training of specialists «Bachelor» and «Master» at specialty «Park Gardening» at the National University of Life and Environmental Sciences of Ukraine
Keywords: зелені насадження міста Луцьк; види деревних рослин; життєздатність; фітосанітарний стан; інвентаризація; фенологічні спостереження; морозостійкість; декоративність; індукція флуоресценції хлорофілу; едафічні умови; green spaces of the city of Lutsk; species of woody plants; viability; phytosanitary condition